The Enlightenment: A century on its way to multiculturalism - Luoma, Virpi (Approaching religion, 2011)
This essay brings out the cultural encounters which characterise the Enlightenment and the contemporary situation. The Enlightenment was an era when cultural encounters were on the rise, but it was also a time when racist attitudes were acceptable. This essay suggests, from a young history student's point of view, how we should deal with contemporary racism and cultural encounters and how can we critically view the racial attitudes which were characteristic of the early modern period.